Annotated list of vascular plants of Zarafshan National Natural Park (Uzbekistan) - Flora Kabulova; Shuhrat Valiev; Noila Jumakulova; Shoxira Atayeva (Acta Biologica Sibirica, 2025)
The article provides an annotated list of vascular plants growing since the beginning of the formation of the Zarafshan State Reserve in 1975 and then in 2018 transferred to another category of protected area – Zarafshan National Natural Park. The list includes 416 plant species belonging to 229 genera and 61 families. One of the serious problems of our time is the degradation of ecosystems, the reduction of biological diversity and the irreparable loss of the gene pool of the plant world. Therefore, protection of the natural environment, accounting and rational use of biological resources is the basis for the development of any state.